Developer's Responsibility To Banks And Customers In Home Ownership Credit (Kpr) Agreements With Buy Back Guarantees - Puspita, Ratna (International Significance of Notary, 2024)
Abstract : Buy back guarantee  is a guarantee from the developer for mortgage repayment provided by the bank to customers / debtors by  buying back housing units purchased by buyers  / customers. In practice,  the buyback made by  the developer from the bank is in accordance with the remaining debt(outstanding) of the last home ownership loan  in the bank. This means  that the buy back guarantee made by the developer is the price of the house  at the time of purchase minus the down payment cost of the house that has  been received by the developer and the installment of home ownership loans that have been received by the  bank  from customers.  The purpose of this study is to analyze the developer's responsibility to banks that provide Home Ownership Loans (KPR) to customers with  a buy back guarantee  and to  analyze the legal protection of customers in buying back guarantees for down payments that have been paid to  developers and credit installments that have been paid to banks.  This research uses  normative juridical research methods or  doctrinal legal research,  namely research that emphasizes the analysis of legal issues by using legal  principles, laws and literature materials related to the legal issues researched and analyzed in this study.The result of this study is the developer's responsibility for banks that provide Home Ownership Loans (KPR) to customers with a buy-back guarantee guarantee is to  carry out a buyback of the house that is collateral by paying the remaining  debt from the customer to the bank. Legal protection for customers  in buying back guarantees for advances that have been paid to developers  and credit installments that have been paid to banks has not been regulated in the legislation, so that  the status of advances in the event of cancellation of the agreement (default) by the buyer is the buyer / customer Cannot ask for back the down payment that has been given to the seller. In addition, the developer only returns  to the buyer/customer the  mortgage installment money that the buyer/customer has paid to the bank, because it is considered a customer's risk as a defaulting debtor.Keywords : Responsibility, Home Ownership Credit, Buy Back Guarantee